2011
DOI: 10.1590/s1677-55382011000600014
|View full text |Cite
|
Sign up to set email alerts
|

Phasic or terminal detrusor overactivity in women: age, urodynamic findings and sphincter behavior relationships

Abstract: Objectives: To search for relationships between phasic (P) and terminal (T) DO with age, urodynamic findings and sphincter behavior during involuntary detrusor contraction in woman. Materials and Methods: Urodynamic studies (triple lumen catheter 7F, seated position) of 164 successive women referred for LUTS with diagnosis of DO were reviewed. Patients were stratified in 4 sub-groups: pre-(18-44 y), peri-(45-54 y), post-menopause (55-74 y) and oldest old (≥ 75 y). The urethral sensor was positioned at the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
1
9
1
Order By: Relevance
“…There are only few clinical publications relating to the different patterns of DO. Two studies showed no significant difference in the incidence of idiopathic or neurogenic DO patterns (TDO vs PDO) in women, although in men TDO dominates . Men and women with PDO pattern of idiopathic DO are significantly younger.…”
Section: What Do We Know From Clinical Studies?mentioning
confidence: 94%
See 2 more Smart Citations
“…There are only few clinical publications relating to the different patterns of DO. Two studies showed no significant difference in the incidence of idiopathic or neurogenic DO patterns (TDO vs PDO) in women, although in men TDO dominates . Men and women with PDO pattern of idiopathic DO are significantly younger.…”
Section: What Do We Know From Clinical Studies?mentioning
confidence: 94%
“…In men, the complaint of urgency is less frequent than in women, with weak association with PDO and TDO. There is a predominance of PDO in IDO and TDO in NDO …”
Section: What Do We Know From Clinical Studies?mentioning
confidence: 99%
See 1 more Smart Citation
“…Joining this specific property with some general results on muscles, we described the excitation at the pressure level as a delayed function of the efferent neurons firing rate F and showed that F is a step function of time except during the end of void . From then, we began to study the process of nervous excitation during detrusor overactivity …”
Section: Part Ii: Clinical Relevancementioning
confidence: 99%
“…The pattern of DO has rarely been taken into account but it has been reported that TDO was more frequent in old women with or without history of neurological disease (4). In men, occurrence of TDO was reported in elderly (5), in patients with Parkinson's disease (6), and the different patterns of DO described in patients with benign prostatic hyperplasia (7,8).…”
Section: Er6 -Université Pierre Et Marie Curie (Paris 06) (Fav Gr); mentioning
confidence: 99%